Gobioecetes biwaensis n. g., n. sp. (Monogenea: Dactylogyridae) from the gills of a freshwater gobiid fish, Rhinogobius sp. BW Takahashi & Okazaki, 2002, with a redescription of Parancyrocephaloides daicoci Yamaguti, 1938. Issue 3 (June 2017) - Ogawa, Kazuo; Itoh, Naoki
Abstract: A description is given of Gobioecetes biwaensis n. g., n. sp. (Monogenea: Dactylogyridae) on the gills ofa freshwater gobiid fish, Rhinogobius sp. BW Takahashi & Okazaki, 2002 from Lake Biwa, Shiga Prefecture and Rhinogobius sp. from Sento Imperial Palace, Kyoto Prefecture, Japan. This monogenean is most similar to Parancyrocephaloides rhinogobius Ling, 1973, proposed here as Gobioecetes rhinogobius n. comb., collected from the gills of Rhinogobius giurinus (Rutter, 1897) in Hupei Province, China, but can be differentiated from it in that ventral hamuli of G . biwaensis are larger than those of G . rhinogobius and in that in G . biwaensis, ventral hamuli are larger than dorsal ones, but in G . rhinogobius, ventral and dorsal hamuli are almost equal in size. The new genus is characterized by the absence of a bar supporting dorsal hamuli. Parancyrocephaloides daicoci Yamaguti, 1938, the type species of the genus, is redescribed based on newly collected specimens from a marine dactylopterid, Dactyloptena peterseni (Nyström, 1887) and the type specimens, revealing that it has a pair of vestigial bars supporting dorsal hamuli. The generic diagnoses of Gobioecetes n. g. and Parancyrocephaloides are given and systematic position of these genera in Dactylogyridae is discussed in this paper. Graphical abstract: Highlights: Gobioecetes biwaensis n. g., n. sp., a monogenean parasite infecting a gobiid fish, Rhinogobius sp. BW. is described. The genus Parancyrocephaloides is emended. Phylogeny of the marine Ancyrocephalinae is discussed.